Exchange trading rules, surveillance and insider trading - Michael Aitken; Douglas Cumming; Feng Zhan (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
We examine the impact of stock exchange trading rules and surveillance on the frequency and severity of suspected insider trading cases in 22 stock exchanges around the world over the period January 2003 through June 2011. Using new indices for market manipulation, insider trading, and broker-agency conflict based on the specific provisions of the trading rules of each stock exchange, along with surveillance to detect non-compliance with such rules, we show that more detailed exchange trading rules and surveillance over time and across markets significantly reduce the number of cases, but increase the profits per case.
urn:nbn:de:hebis:30:3-324924
Keywords: G12; G14; G18; K22; 330; Insider trading; Surveillance; Exchange Trading Rules; Law and Finance